# -7s+1=-9s+2(s-1)

## Simple and best practice solution for -7s+1=-9s+2(s-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for -7s+1=-9s+2(s-1) equation:

Simplifying
-7s + 1 = -9s + 2(s + -1)

Reorder the terms:
1 + -7s = -9s + 2(s + -1)

Reorder the terms:
1 + -7s = -9s + 2(-1 + s)
1 + -7s = -9s + (-1 * 2 + s * 2)
1 + -7s = -9s + (-2 + 2s)

Reorder the terms:
1 + -7s = -2 + -9s + 2s

Combine like terms: -9s + 2s = -7s
1 + -7s = -2 + -7s

Add '7s' to each side of the equation.
1 + -7s + 7s = -2 + -7s + 7s

Combine like terms: -7s + 7s = 0
1 + 0 = -2 + -7s + 7s
1 = -2 + -7s + 7s

Combine like terms: -7s + 7s = 0
1 = -2 + 0
1 = -2

Solving
1 = -2

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.`